DEAE- Cellulose-based composite hydrogel for 3D printing application: Physicochemical, mechanical, and biological optimization. (December 2022) - Vel, Rathina; Bhatt, Anugya; Priyanka, A.; Gauthaman, Ashna; Anilkumar, V.; Safeena, A.S.; S, Ranjith
Abstract: 3D bioprinting is a layer-by-layer additive manufacturing process that requires the incorporation of biomaterials, cells, growth factors, etc. The biomaterial-ink used in bioprinting should comprise essential properties like shear thinning, proper viscosity and reduced shear stress on cells, structural integrity, porosity, biocompatible and degradable, etc., Especially in extrusion-based bioprinting, optimization of biomaterial ink is critical. Even though single-aspect biomaterials have been used for establishing a biomaterial ink, however, they often fail to meet all properties needed to be used as a biomaterial ink. Carrying this point in view, we have formulated hydrogels using Diethylaminoethyl Cellulose (DEAE-Cellulose), Alginate (ALG), and Gelatin (GEL) as biomaterial inks. Initially, six different hydrogel formulations (F1-F6) were prepared with varying concentrations of DEAE- Cellulose (0.45%−2%), alginate (1%−2%), and keeping gelatine concentration constant at 3.33%. These formulations were then assayed by swelling and degradation tests. Out of six, three hydrogels (F3, F4, and F5) were eliminated after initial studies due to the rapid degradation rate. The other three hydrogels ( F1, F2, and F6) were further thoroughly analyzed by the rheological study, mechanical study, printability assay, morphological analysis, and biocompatibility assays. Here, We have demonstrated the successful formulation of three biomaterial inks utilizing three different biopolymers for the field of tissue engineering with adequate swelling, degradation, rheological and printability properties. It was observed that the incorporation of DEAE-Cellulose significantly improved the shear thinning and viscosity recovery of hydrogels. Also, it improves mechanical integrity and printing accuracy. Moreover, all three hydrogels have shown excellent hemocompatibility and cytocompatibility. To conclude, this study proposes the optimization of composite hydrogel for 3D printing applications. Graphical Abstract: ga1